Neck moment characterization of restrained child occupant at realistic nontest standard higher impact speed of 32.2 km/h - Shasthri, Sevaguru; Venkatason, Kausalyah; Shah, Qasim Hussain; Abdullah, Kassim Abdulrahman; Idres, Moumen; Wong, Sha Voon (Hindawi Publishing Corporation, 2014)
The effects of bullet vehicle crash impact angle, child restraint system design, and restraint harness slack at side impact speed of 32.2 km/h (20mph) on moments sustained at the neck by a three-year-old child are investigated. Mathematical models are built using the response surface method based on simulation results whereby good fitness is achieved. The singular and cross interactive effect of each predictor on the neck moment are analyzed. The number of significant parameters affecting the neck moment is shown to be the largest for wide impact angles (